Detection of antibodies to human parvovirus in erythema infectiosum (fifth disease). Issue 11 (November 1984) - Okabe, N; Koboyashi, S; Tatsuzawa, O; Mortimer, P P
Abstract : Two Japanese outbreaks of erythema infectiosum were investigated for evidence of human parvovirus infection by a solid phase antibody capture radioimmunoassay based on a monoclonal antibody to human parvovirus. Specific IgM and high concentrations of specific IgG were detected in 37 sera from 27 children with erythema infectiosum. No anti human parvovirus IgM was detected in a remaining case of erythema infectiosum, in five patients with Kawasaki disease, or in the 17 control children. Seven of the controls were also anti human parvovirus IgG negative, and the 10 who were seropositive had lower concentrations of anti human parvovirus IgG than the patients with erythema infectiosum. These data indicate that human parvovirus is a cause of erythema infectiosum.